Directing T-Cell Immune Responses for Cancer Vaccination and Immunotherapy - Peter Lawrence Smith; Katarzyna Piadel; Angus George Dalgleish (Vaccines, 2021)
Cancer vaccination and immunotherapy revolutionised the treatment of cancer, a result of decades of research into the immune system in health and disease. However, despite recent breakthroughs in treating otherwise terminal cancer, only a minority of patients respond to cancer immunotherapy and some cancers are largely refractive to immunotherapy treatment. This is due to numerous issues intrinsic to the tumour, its microenvironment, or the immune system. CD4+ and CD8+ αβ T-cells emerged as the primary effector cells of the anti-tumour immune response but their function in cancer patients is often compromised. This review details the mechanisms by which T-cell responses are hindered in the setting of cancer and refractive to immunotherapy, and details many of the approaches under investigation to direct T-cell function and improve the efficacy of cancer vaccination and immunotherapy.